Gene expression of Hsps in normal and abnormal embryonic development of mouse hindlimbs. (June 2015) - Yan, Zhengli; Wei, Huimiao; Ren, Chuanlu; Yuan, Shishan; Fu, Hu; Lv, Yuan; Zhu, Yongfei; Zhang, Tianbao
Heat shock proteins (Hsps), which have important biological functions, are a class of highly conserved genetic molecules with the capacity of protecting and promoting cells to repair themselves from damage caused by various stimuli. Our previous studies found that Hsp25, HspB2, HspB3, HspB7, Hsp20, HspB9, HspB10, and Hsp40 may be related to all-trans retinoic acid (atRA)-induced phocomelic and other abnormalities, while HspA12B, HspA14, Trap1, and Hsp105 may be forelimb development-related genes; Grp78 may play an important role in forelimb development. In this study, the embryonic phocomelic, oligodactylic model of both forelimbs and hindlimbs was developed by atRA administered per os to the pregnant mice on gestational day 11, and the expression of 36 members of Hsps family in normal and abnormal development of embryonic hindlimbs was measured by real-time fluorescent quantitative polymerase chain reaction (qRT-PCR). It is found that HspA1L, Hsp22, Hsp10, Hsp60, Hsp47, HspB2, HspB10, HspA12A, Apg1, HspB4, Grp78, and HspB9 probably performs a major function in limb development, and HspA13, Grp94 and Hsp110 may be hindlimb development-related genes.